Incidence and influencing factors of tooth discoloration in children using doxycycline: a meta-analysis - Ma, Kun; Lu, Mingjing; Li, Hao; Yuan, Xin; Zhang, Ying; Ni, Qiuying; Li, Yun; Dong, Xiaolin; Guo, Jingjing (Frontiers in Pediatrics, 2025)
Doxycycline is traditionally avoided in children under 8 years due to concerns about permanent tooth discoloration. This meta-analysis aimed to assess the incidence of tooth discoloration in children treated with doxycycline and identify influencing factors. A systematic search of PubMed, Embase, Web of Science, Wanfang, and CNKI was conducted up to January 14, 2025, for studies reporting tooth discoloration in children (<18 years) treated with doxycycline. Pooled incidence was estimated using a random-effects model. Subgroup and univariate meta-regression analyses explored potential modifiers. Seventeen studies comprising 1,025 children were included. The pooled incidence of tooth discoloration was 0.92% (95% CI: 0.34%–1.50%) with no significant heterogeneity (I² < 0%). Subgroup analyses showed no significant differences by region, study design, age group, administration route, or assessment method. Meta-regression indicated no significant effects from publication year, sample size, mean age, dose, treatment duration, follow-up length, or study quality. The incidence of tooth discoloration following doxycycline use in children is low. These findings support the potential safety of doxycycline in pediatric populations, including those under 8 years of age, when clinically warranted.Systematic Review RegistrationPROSPERO (CRD420251009690).